Scientific Truth: Essence, Types, Approaches and Theories of Truth - Husnul Yamil; Abdul Fatah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Scientific truth is the primary foundation in the process of developing science. This article comprehensively discusses the nature of scientific truth, the various types of truth, the approaches used in the process of discovering truth, and the theories underlying the validity of knowledge. The discussion begins with an analysis of the characteristics of scientific truth: objective, rational, systematic, and testable. Next, the article outlines the types of truth, including coherent, correspondence, pragmatic, and consensus truth. Scientific approaches such as empirical, rational, critical, and hermeneutical approaches are also explained as frameworks for acquiring and verifying knowledge. Finally, the main theories of truth-correspondence, coherence, pragmatic, performative, and constructivist-are examined to demonstrate how each theory provides a different perspective in assessing the validity of scientific propositions. This article emphasizes the importance of a comprehensive understanding of scientific truth so that research is valid, accountable, and relevant to the development of science.